The electric light and the future: American perceptions and expectations, 1879-1890. - McDonnell, Joel W. (University of Ottawa (Canada), 1997)
This thesis explores the manner in which electric lighting was applied during the first decade after Edison's Menlo Park demonstration, and how these applications influenced American public perceptions of the technology, particularly in relation to imagined future uses and social meanings. Specifically, the thesis focuses on expectations and perceptions of electric lighting as applied or related to three important aspects of late nineteenth century American society: crime, warfare, and aesthetics and health. Using these three themes, this thesis illustrates how electric lighting was viewed during the 1880's and what hopes and images were attached to it.
Keywords: History, United States.